Comparative risk of adverse perinatal outcomes associated with classes of antiretroviral therapy in pregnant women living with HIV: systematic review and meta-analysis - Beck, Katharina; Cowdell, Imogen; Portwood, Clara; Sexton, Harriet; Kumarendran, Mary; Brandon, Zoe; Kirtley, Shona; Hemelaar, Joris (Frontiers in Medicine, 2024)
Background Integrase strand transfer inhibitor (INSTI) dolutegravir (DTG)-based antiretroviral therapy (ART) is recommended by World Health Organisation as preferred first-line regimen in pregnant women living with human immunodeficiency virus (HIV) (WLHIV). Non-nucleoside reverse transfer inhibitor (NNRTI)-based ART and protease inhibitor (PI)-based ART are designated as alternative regimens. The impact of different ART regimens on perinatal outcomes is uncertain. We aimed to assess the comparative risk of adverse perinatal outcomes in WLHIV receiving different classes of ART. Materials and methods A systematic literature review was conducted by searching PubMed, CINAHL, Global Health, and EMBASE for studies published between Jan 1, 1980, and July 14, 2023. We included studies reporting on the association of pregnant WLHIV receiving different classes of ART with 11 perinatal outcomes: preterm birth (PTB), very PTB, spontaneous PTB, low birthweight (LBW), very LBW, term LBW, preterm LBW, small for gestational age (SGA), very SGA (VSGA), stillbirth, and neonatal death. Pairwise random-effects meta-analyses compared the risk of each adverse perinatal outcome among WLHIV receiving INSTI-ART, NNRTI-ART, PI-ART, and nucleoside reverse transfer inhibitor (NRTI)-based ART, and compared specific “third drugs” from different ART classes. Subgroup and sensitivity analyses were conducted based on country income status and study quality. Results Thirty cohort studies published in 2006–2022, including 222,312 pregnant women, met the eligibility criteria. Random-effects meta-analyses found no evidence that INSTI-ART is associated with adverse perinatal outcomes compared to NNRTI-ART and PI-ART. We found that PI-ART is associated with a significantly increased risk of SGA (RR 1.28, 95% confidence interval (95% CI) [1.09, 1.51], p = 0.003) and VSGA (RR 1.41, 95% CI [1.08, 1.83], p = 0.011), compared to NNRTI-ART. Specifically, lopinavir/ritonavir (LPV/r) was associated with an increased risk of SGA (RR 1.40, 95% CI [1.18, 1.65], p = 0.003) and VSGA (RR 1.84, 95% CI [1.37, 2.45], p = 0.002), compared to efavirenz, but not compared to nevirapine. We found no evidence that any class of ART or specific “third drug” was associated with an increased risk of PTB. Conclusion Our findings support the recommendation of INSTI-ART as first-line ART regimen for use in pregnant WLHIV. However, the increased risks of SGA and VGSA associated with PI-ART, compared to NNRTI-ART, may impact choice of second- and third-line ART regimens in pregnancy. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42021248987.